New Results on I2-Statistically Limit Points and I2-Statistically Cluster Points of Sequences of Fuzzy Numbers. (10th November 2021) - Kişi, Ö.; Huban, M. B.; Gürdal, M.
Abstract : In this paper, some existing theories on convergence of fuzzy number sequences are extended to I 2 -statistical convergence of fuzzy number sequence. Also, we broaden the notions of I -statistical limit points and I -statistical cluster points of a sequence of fuzzy numbers to I 2 -statistical limit points and I 2 -statistical cluster points of a double sequence of fuzzy numbers. Also, the researchers focus on important fundamental features of the set of all I 2 -statistical cluster points and the set of all I 2 -statistical limit points of a double sequence of fuzzy numbers and examine the relationship between them.